Effectiveness of the Extension Programs of the BS Mathematics Program of Pangasinan State University – Lingayen - Cruz, Flerida Regine; Santillan, Coreta (Southeast Asian Journal of Science and Technology, 2022)
This paper aimed to assess the effectiveness of the implemented extension activities of the BS Mathematics Program of Pangasinan State University Lingayen in different partner barangay high schools, Salomague National High School and Polong National High School, in Bugallon, Pangasinan. This descriptive research study used survey questionnaires. A 5-point Likert scale was used to assess the opinions of the respondents. The respondents’ answers were tabulated and then averages were taken to determine the satisfaction of the respondents on the effectivity of the conducted extension activities. Results show that the beneficiaries, both the students and teachers, strongly agree that they have benefited from and been impacted by the Mathematics Department’s extension operations.